Elimination of Mother-to-child Transmission of Syphilis: Challenge and Solution. Issue 2 (15th October 2019) - Fan, Shang-Rong; Wang, Ai-Ling; Wang, Lin-Hong
Abstract : Abstract: Congenital syphilis (CS) is a significant public health problem worldwide. The majority of cases of CS are caused by in utero transmission. The World Health Organization launched the global elimination of CS initiative with the goal of reducing mother-to-child transmission of syphilis. The risk for CS is mainly related to three factors: (1) high maternal prevalence, (2) low coverage of antenatal care services, and (3) treatment failure. The long-acting penicillin preparations such as benzathine penicillin G are the preferred therapies for maternal syphilis. There are several challenges in preventing CS from both pregnant women and their health care providers. These problems include that prenatal care lack or delay, syphilis management flaws from health care providers, lacks of basic information, and awareness about maternal syphilis and CS by public. Many efforts have been made to solve the problems. These include that dual elimination of mother-to-child transmission (EMTCT) of both human immunodeficiency virus (HIV) and syphilis or triple EMTCT of HIV, syphilis and hepatitis B, World Health Organization country validation of EMTCT of syphilis and HIV, set up a CS case review board and a National Day to combat syphilis and CS.